Estudo para Compartilhamento de Terminais entre um Sistema Tronco-Alimentador de Passageiros e a Logística Urbana de Cargas - Vieira, Jardel Inácio Moreira (2015)
The objective of this study is to analyze the feasibility of using part of the capacity of its vehicles outside their peak hours in urban logistics charges. The resource sharing proposal seeks to reduce costs and improve both the quality of its vehicles, specifically overcrowding at peak times. The Bus Rapid Transit (BRT) system in the trunk-feeder configuration for passenger and freight of Urban Logistics terminals using overflow Peripherals Loads of Urban Vehicles (VUC) use similar physical resources, specifically peripheral terminals near urban expressways. The study used data from a shipping company that carries out about 100 daily deliveries of fractional loads for trades in Uberlândia - MG. The Logistics tools were applied (Transportation Problem and Minimum Cost Flow) and routing (Vehicle Routing) of TransCAD system on a road network where they are stationed peripheral terminals of the Integrated Transport System (passengers) and the clients served by the carrier. The computer simulation scaled the fleet that can meet the daily demand of the carrier traveling during a time window equivalent to window time low demmand passenger transport.